2006
DOI: 10.1017/s1481803500013671
|View full text |Cite
|
Sign up to set email alerts
|

Chest Pain in Emergency Department Patients: If the Pain is Relieved by Nitroglycerin, is it More Likely to be Cardiac Chest Pain?

Abstract: Introduction:It is often believed that chest pain relieved by nitroglycerin is indicative of coronary artery disease origin. Objective: To determine if relief of chest pain with nitroglycerin can be used as a diagnostic test to help differentiate cardiac chest pain and non-cardiac chest pain. Design: Prospective observational cohort study with a 4-week follow-up of patients enrolled. Setting: Academic tertiary care hospital, with 60 000 visits/year. Inclusion criteria: Adult patients presenting to the emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Five studies (LOE D3 68,78,105 ; LOE D4 106,107 ) using reduction in pain after nitroglyercin administration as an end point, found that reduction of pain does not reliably identify presence of ACS.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Five studies (LOE D3 68,78,105 ; LOE D4 106,107 ) using reduction in pain after nitroglyercin administration as an end point, found that reduction of pain does not reliably identify presence of ACS.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Another common belief is that if a patient's ANTCP is relieved by GTN then it is likely of cardiac origin. Contradicting this belief, several studies have shown there is no correlation between relief of NTCP with GTN and ACS or CAD (35)(36)(37)(38)(39) and has an unhelpful LR of 1.1 (22).…”
Section: Use Of Glyceryl Trinitratementioning
confidence: 99%
“…A cautionary note also applies to the use of a response to sublingual nitroglycerine therapy as a diagnostic manoeuvre 3–6 . (Class B;LOE IV).…”
Section: Symptoms and Signsmentioning
confidence: 99%